Kreasi Bersama Vendor dan Pengelola Food Court dalam Menciptakan Strategi Baru Meningkatkan Kepuasan Pelanggan - Sinaga, Lamtiar; Syahza, Almasdi; Asmit, Brilliant (Universitas Mataram, 2024)
This study aims to analyze the application of the marketing mix in enhancing customer satisfaction in the Riau Garden Food Court, Pekanbaru. Using a qualitative method with a grounded theory approach, the research involved 14 informants, including culinary business owners and customers. Data were collected through interviews, observations, and documentation, and analyzed using open, axial, and selective coding techniques. The results indicate that the 4P marketing mix (product, price, promotion, and place) has been implemented but remains suboptimal. Customers expressed satisfaction with the variety of products, unique flavors, and the strategic and comfortable location. However, dissatisfaction arose concerning high prices and subpar promotional efforts. This study recommends improving pricing strategies with affordable options and enhancing promotion through consistent social media efforts. These findings provide new insights into the importance of collaboration between food court managers and business owners to optimize the marketing mix and boost customer satisfaction.